PENGARUH LATIHAN SMALL SIDE GAME TERHADAP KETEPATAN PASSING CLUB PS ROBATAL - Moh. Sulton; Haryo Mukti Widodo; Septyaningrum Putri Purwoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve passing accuracy through Small-Sided Games training at Club PS ROBATAL. This research is using experimental method. The research design used is Pre-Experimental, specifically One-Group Pretest-Posttest Design. The sample for this research was 20 players from the PS Robatal Club. This research instrument uses the Passing Accuracy Test, which is a standard test that measures passing accuracy in various situations. Scores are given based on accuracy and speed of passing to the specified target. Data analysis was carried out using SPSS 21. From the calculation results, the calculated t value was 7.581, which was greater than the t table value, namely 1.729. Apart from that, the probability significance value is 0.000 which is smaller than 0.05. From the mean difference value of 2.7, it can be concluded that the Small-Sided Games training method provides a significant change in passing accuracy, with an average of 2,700 more correct balls to friends than before training and also a percentage increase of 31.04%. The conclusion of this research is that there is a significant increase in results in treatment using the Small-Sided Games training model.